2011
DOI: 10.5694/j.1326-5377.2011.tb04195.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in Aboriginal Australians

Abstract: Objective: To investigate the adequacy of vitamin D status in a South Australian Aboriginal population, and to examine the relationship between serum 25‐hydroxyvitamin D (25‐OHD) levels and biochemical variables of calcium and bone mineral homeostasis, as well as other factors which may influence vitamin D synthesis, storage and metabolism. Design, setting and participants: A single‐visit, observational study of 58 adults from two Aboriginal community‐controlled health services in Adelaide and Yalata, South Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
3
25
1
Order By: Relevance
“…The overall mean 25-OHD level (74.0 nmol/l) found in this audit was similar to the 76.9 nmol/l mean level found in a group of Adelaide residents[4] and higher than the 56.8 nmol/l mean level found in a recent study of adult Aboriginal Australians[5]. Furthermore, the audit confirmed the known seasonal variation in 25-OHD [5] by finding a high proportion of 25-OHD tests taken in summer compared to other seasons and a comparatively low proportion of patients with low levels of 25-OHD in summer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall mean 25-OHD level (74.0 nmol/l) found in this audit was similar to the 76.9 nmol/l mean level found in a group of Adelaide residents[4] and higher than the 56.8 nmol/l mean level found in a recent study of adult Aboriginal Australians[5]. Furthermore, the audit confirmed the known seasonal variation in 25-OHD [5] by finding a high proportion of 25-OHD tests taken in summer compared to other seasons and a comparatively low proportion of patients with low levels of 25-OHD in summer.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the audit confirmed the known seasonal variation in 25-OHD [5] by finding a high proportion of 25-OHD tests taken in summer compared to other seasons and a comparatively low proportion of patients with low levels of 25-OHD in summer. In our audit, we did not measure the amount of time patients spent outside.…”
Section: Discussionsupporting
confidence: 65%
“…We have reported a high percentage (31%) of vitamin D deficiency in this cohort from Northern and Central Australia, regions closer to the equator than previous Australian studies. The median 25(OH)D level (55 nmol/L) is similar to the mean 25(OH)D previously reported in a small study of 58 Aboriginal participants from South Australia (latitude 35 degrees south), of 56.8 nmol/L [12]. Of note, AusDiab, a nation-wide Australian population-based study, reported that 31% of Australians had 25(OH)D levels <50 nmol/L, however only 0.9% of AusDiab participants identified as Aboriginal or Torres Strait Islander Australians [6].…”
Section: Discussionsupporting
confidence: 85%
“…A recent systematic review reported a prevalence of 30-53% in ethnic minorities with dark skin versus 14-26% in those of Europid background [11]. Limited data from South Australia show that Indigenous Australians have a low vitamin D status [12]. However, approximately 40% of Indigenous Australians live at latitudes closer to the equator - in the tropical and subtropical regions of Australia [13].…”
Section: Introductionmentioning
confidence: 99%
“…The IOM’s concern about skin cancer precluded them from making recommendations about sun exposure even though they acknowledged that casual sun exposure played an important role in a person’s vitamin D status. Humans have and continue to obtain a significant amount of their vitamin D requirement from sun exposure 7 , 10 , 11 , 17 , 42 . Although excessive exposure to sunlight increases risk for nonmelanoma skin cancer which is easy to detect and easy to treat there is no evidence that sensible sun exposure, as our hunter gatherer forefathers likely experienced, increases risk.…”
mentioning
confidence: 99%